The response of aluminium and glass fibre FMLS subjected to blast loading - Volschenk, Gideon (Department of Mechanical Engineering, 2015)
Fibre-Metal Laminates (FMLs) have long been of interest to the aeronautics industry due to their exceptional strength to weight ratio, fatigue and impact resistance. Due to the increasing global risk of subversive activity in this industry, the focus of research in recent years has shifted to the blast resistance of these materials. A particularly interesting material being GLARE, a commercially available Aluminium-GFRP FML. This dissertation presents the results of an experimental study into the effects of glass fibre configuration and epoxy type on the response of glass fibre reinforced, epoxy-based FMLs, subjected to localised and uniform blast loading conditions. Standard tensile specimens and Single-Leg Bend (SLB) specimens were manufactured and tested to determine the properties constitutive materials and interfacial bond strength. Bond strength between the composite and metal interfaces was improved by employing a combination of surface treatments, consisting of both mechanical and chemical as well as the use of a film adhesive. FMLs were manufactured from Al 2024-T3 and e-glass fibre reinforced epoxy composite. Both woven and unidirectional fibre configurations were used as part of either a prepreg or wet layup to construct the composite layers. Tensile and SLB specimens were used to characterise the constitutive materials and interfacial bond strength. SLB tests were used to determine the effect of cure cycle and composite layup technique on interfacial bond strength. These tests and revealed a variety of interfacial failure modes for different cure cycles and epoxy configurations, each resulting in different levels of strength. The modes, in increasing order of strength, included debonding of the film adhesive from either the metal or composite interface or both, and in some cases also included delamination in the composite layer. Tests showed that a single stage layup and cure cycle resulted in the strongest bonds between interfaces, compared to a multi-stage manufacturing processes. It was also shown that the use of prepreg resulted in stronger inter-facial bonds than a wet-layup process. The properties of the constitutive materials were used to construct a numerical model to aid in experimental design. The model was used to determine a suitable range of charge masses for testing.